THE CONTRIBUTION OF ZAKAT TO NATIONAL INCOME IN MALAYSIA - Noor Azizah Beddu; Mohd Ali Mohd Noor (Journal of Islamic, Social, Economics and Development, 2018)
National Income (GDP) is a typical indicator of the wealth of a country. However,the expenditure method used to measure the country's wealth only takes into account some ofthe key components of expenditure such as consumption (C), investment (I), governmentspending (G) and net export (X-M). In the Islamic Economic System, expenditures incurred toassist the poor need to be taken into account as a (C) consumption in state revenue. This issupported by the literature study that zakat is an important instrument that can contribute tothe consumption expenditure and ultimately to national income. Because there is no empiricalstudy yet which shows the contribution of zakat to Malaysian income, this study is conductedto meet this gap using econometric methods; Ordinary Lease Square (OLS). The study foundthat there was a positive relationship between zakat and Malaysian income.